Pengaturan Cohabitation dalam Hukum Pidana Nasional: Antara Moralitas dan Legalitas - Ismail, Zulkifli; Lestari, Melanie Pita; Ahmad, Ahmad (KAMPUS AKADEMIK PUBLISING, 2026)
The phenomenon of cohabitation, defined as living together outside a legally recognized marriage, has increasingly emerged as a social reality alongside shifting relational patterns and value systems in modern society. This development has generated ongoing debates regarding the extent to which the state may legitimately intervene in the realm of private morality through criminal law. This study aims to analyze the regulation of cohabitation within the national criminal law framework, both in the context of the absence of explicit regulation under the former Criminal Code (KUHP) and the implications of morality-based provisions under the new National Criminal Code, as well as to assess the rationality of its criminalization from the perspectives of modern criminal law and human rights. This research employs a normative legal method using statutory, conceptual, and philosophical approaches, drawing upon legislation, criminal law doctrines, and relevant scholarly literature. The findings indicate that the criminalization of cohabitation has the potential to generate tension between public morality and the principle of legality, particularly in relation to the doctrines of ultima ratio, proportionality, and legal certainty. Moreover, overly broad regulatory formulations may create opportunities for abuse of authority and risk infringing upon the rights to privacy and individual freedom. Accordingly, this study recommends that criminal law policy formulation adopt a limited and selective approach to state intervention, oriented toward the protection of concrete legal interests, in order to avoid overcriminalization in the domain of private morality. Keywords: cohabitation, criminal law, morality, legality principle, human rights.